Phage P2-71 against multi-drug resistant Proteus mirabilis: isolation, characterization, and non-antibiotic antimicrobial potential - Dong, Zhiyou; Wu, Ruihu; Liu, Lijuan; Ai, Shengquan; Yang, Jinpeng; Li, Qianlan; Fu, Keyi; Zhou, Yunian; Fu, Hualin; Zhou, Ziyao; Liu, Haifeng; Zhong, Zhijun; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Proteus mirabilis, a prevalent urinary tract pathogen and formidable biofilm producer, especially in Catheter-Associated Urinary Tract Infection, has seen a worrying rise in multidrug-resistant (MDR) strains. This upsurge calls for innovative approaches in infection control, beyond traditional antibiotics. Our research introduces bacteriophage (phage) therapy as a novel non-antibiotic strategy to combat these drug-resistant infections. We isolated P2-71, a lytic phage derived from canine feces, demonstrating potent activity against MDR P. mirabilis strains. P2-71 showcases a notably brief 10-minute latent period and a significant burst size of 228 particles per infected bacterium, ensuring rapid bacterial clearance. The phage maintains stability over a broad temperature range of 30-50°C and within a pH spectrum of 4-11, highlighting its resilience in various environmental conditions. Our host range assessment solidifies its potential against diverse MDR P. mirabilis strains. Through killing curve analysis, P2-71’s effectiveness was validated at various MOI levels against P. mirabilis 37, highlighting its versatility. We extended our research to examine P2-71’s stability and bactericidal kinetics in artificial urine, affirming its potential for clinical application. A detailed genomic analysis reveals P2-71’s complex genetic makeup, including genes essential for morphogenesis, lysis, and DNA modification, which are crucial for its therapeutic action. This study not only furthers the understanding of phage therapy as a promising non-antibiotic antimicrobial but also underscores its critical role in combating emerging MDR infections in both veterinary and public health contexts.